Assessment of Efficacy and Safety of Arterolane Maleate–Piperaquine Phosphate Dispersible Tablets in Comparison With Artemether-Lumefantrine Dispersible Tablets in Pediatric Patients With Acute Uncomplicated Plasmodium falciparum Malaria: A Phase 3, Randomized, Multicenter Trial in India and Africa. (29th August 2017) - Toure, Offianan Andre; Mwapasa, Victor; Sagara, Issaka; Gaye, Oumar; Thompson, Ricardo; Maheshwar, Aishwarya V; Mishra, Pitabas; Behra, Narendra; Tshefu, Antoinette K; Das, Rashmi R; Anvikar, Anupkumar R; Sharma, Pradeep; et al.
Abstract : In East Africa, data on the risk and predictors of visceral leishmaniasis relapse in HIV coinfected patients are scarce. This study shows high risk of relapse, particularly in those not on antiretroviral therapy or with a high tissue parasite load. Abstract: Background: Administration of artemisinin-based combination therapy (ACT) to infant and young children can be challenging. A formulation with accurate dose and ease of administration will improve adherence and compliance in children. The fixed-dose combination dispersible tablet of arterolane maleate (AM) 37.5 mg and piperaquine phosphate (PQP) 187.5 mg can make dosing convenient in children. Methods: This multicenter (India and Africa), comparative, parallel-group trial enrolled 859 patients aged 6 months to 12 years with Plasmodium falciparum malaria. Patients were randomized in a ratio of 2:1 to AM-PQP (571 patients) once daily and artemether-lumefantrine (AL) (288 patients) twice daily for 3 days and followed for 42 days. Results: The cure rate (ie, polymerase chain reaction–corrected adequate clinical and parasitological response) in the per-protocol population at day 28 was 100.0% and 98.5% (difference, 1.48% [95% confidence interval CI, .04%–2.91%]) in the AM-PQP and AL arms, respectively, and 96.0% and 95.8% (difference, 0.14% [95% CI, –2.68% to 2.95%]) in the intention-to-treat (ITT) population. The cure rate was comparable at day 42 in the ITT population (AM-PQP, 94.4% vs AL, 93.1%). The median parasite clearance time was 24 hours in both the arms. The median fever clearance time was 6 hours in AM-PQP and 12 hours in the AL arm. Both the treatments were found to be safe and well tolerated. Overall, safety profile of both the treatments was similar. Conclusions: The efficacy and safety of fixed-dose combination of AM and PQP was comparable to AL for the treatment of uncomplicated P. falciparum malaria in pediatric patients. Clinical Trials Registration: CTRI/2014/07/004764.